ENGLISH-SPANISH CODE SWITCHING IN NETFLIX’S ONE DAY AT A TIME - Ramadhani, Nataliashefa Putri; Wisasongko, Wisasongko; Wahyuningsih, Indah (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2024)
This research examines the English-Spanish languange code switching performed by the main characters in the series One Day At A Time using Holmes’ theory. The study analyzes four primary factors driving the use of code switching by the main characters in the series: identity, social, topic, and function. Qualitative research was conducted by collecting and analyzing data from the subtitles of Netflix’s One Day At A Time season 1, 4 episodes. 25 dialogues containing code switching were carefully selected and analyzed to uncover the factors behind the code switching performed by the main characters. Among the four factors, the results of the research reveal that function factors are the most function used, which appearing in 22 dialogues. Followed by social factors in the second place with 13 dialogues. Identity factors ranked third, present in 12 dialogues, and topic factors appear in only 1 dialogue. In conclusion, this study unveils how the main characters employ code switching to navigate their bilingual environment based on the aspects of four factors. This discussion enriches the readers’ understanding of code switching within a multicultural framework.